An application of the Fourier transform to optimization of continuous 2-D systems - Dymkou, Vitali; Dymkov, Michael (Zielona Góra: Uniwersytet Zielonogórski)
This paper uses the theory of entire functions to study the linear quadratic optimization problem for a class of continuous 2D systems. We show that in some cases optimal control can be given by an analytical formula. A simple method is also proposed to find an approximate solution with preassigned accuracy. Some application to the 1D optimization problem is presented, too. The obtained results form a theoretical background for the design problem of optimal controllers for relevant processes.
Keywords: 2D systems; optimization; entire functions; Fourier transform; approximation